1987
DOI: 10.2135/cropsci1987.0011183x002700010007x
|View full text |Cite
|
Sign up to set email alerts
|

Pollen Viability, Pollen Shedding, and Combining Ability for Tassel Heat Tolerance in Maize1

Abstract: High temperatures during maize (Zea mays L.) pollination limit kernel number. Knowledge is limited on the effect of heat stress on both pollen viability and tassel shedding characteristics or of possible heat tolerance sources and testers. The purpose of this research was to determine the tassel response to heat stress, as measured by in vitro pollen viability and shedding characteristics, and the combining ability for these traits using a diallel of four heat‐tolerant and three heat‐intolerant inbreds. Tassel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
59
1
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 0 publications
0
59
1
1
Order By: Relevance
“…High temperature during the reproductive phase is associated with a decrease in yield due to a decrease in the number of grains and kernel weight. Under high temperatures, the number of ovules that are fertilized and develop into grain decreases (Schoper et al, 1987a and b). A comparison of the response of male and female reproductive tissues to heat stress demonstrated that female tissues have greater tolerance (Dupis and Durnas, 1990).…”
Section: Heatmentioning
confidence: 99%
See 1 more Smart Citation
“…High temperature during the reproductive phase is associated with a decrease in yield due to a decrease in the number of grains and kernel weight. Under high temperatures, the number of ovules that are fertilized and develop into grain decreases (Schoper et al, 1987a and b). A comparison of the response of male and female reproductive tissues to heat stress demonstrated that female tissues have greater tolerance (Dupis and Durnas, 1990).…”
Section: Heatmentioning
confidence: 99%
“…Pollen production and/or viability have been highlighted as major factors responsible for reduced fertilisation under high temperatures. Pollen produced under high temperature has reduced viability and in vitro germination (Herrero and Johnson, 1980;Schoper et al, 1986;Schoper et al, 1987a and b;Dupis and Durnas, 1990). Additionally, high temperatures are responsible for reduced pollen water potential, quantity of the pollen shed and pollen tube germination (Schoper et al, 1987;Dupis and Durnas, 1990).…”
Section: Heatmentioning
confidence: 99%
“…The methods used to study gene flow include potential pollen-mediated gene flow (which includes the analysis of pollen viability, pollen dispersal and deposition, pollen capture and computer modelling) [17][18][19][20][21][22][23][24][25][26] and pollen-mediated gene flow (which involves determining the extent of cross-pollination over distance and computer modelling) [27][28][29][30][31][32][33][34][35][36][37][38]. While several studies have determined the extent of cross-pollination at different distances ranging from 34 to 650 m, it is not certain how applicable these data are to the maize growing region of South Africa.…”
Section: Introductionmentioning
confidence: 99%
“…In maize (Zea mays), ovary development is highly drought sensitive (Boyer and Westgate, 2004) while pollen viability is not (Herrero and Johnson, 1981;Schoper et al, 1986Schoper et al, , 1987. A disruption of carbon metabolism in ovaries has been suggested to be the main cause of abortion, based on a series of experiments showing that Suc feeding can partly reverse the effect of WD on abortion (Boyle et al, 1991;Zinselmeier et al, 1995aZinselmeier et al, , 1999McLaughlin and Boyer, 2004).…”
mentioning
confidence: 99%